Dolichogenidea glyphodes, sp. nov. (Hymenoptera: Braconidae: Microgastrinae), a parasitoid of Glyphodes caesalis (Walker) (Lepidoptera: Crambidae) - Dat, Do Xuan; Long, Khuat Dang; Dzung, Lai Tien (Zootaxa, 2026)
One new species of the genus Dolichogenidea Viereck, 1911, Dolichogenidea glyphodes Long & Dat, sp. nov., is described and fully illustrated based on series of specimens collected from gregarious cocoons of borers feeding on jackfruits, Glyphodes caesalis (Walker, 1859). The new species appears to be relatively specialized on their host species, parasitizing caterpillars of Crambidae infesting jackfruits (Artocarpus spp.)